Numerical Analysis for Determination of Hydrodynamic Characteristics of a Gimbaled Thrust Vectoring Nozzle (Journal of Bangladesh Academy of Sciences, 2017)
Gimbaled thrust vectoring nozzles are employed in Solid Rocket Motors (SRM) to account for the aspects of maneuverability of the flight vehicle. The flow field of such a solid pulsed rocket motor is explored numerically (from dome-closeout onward) by solving Reynolds-averaged Navier-Stokes equations with Menters Shear Stress Transport (SST) k - ? turbulence model using a Computational Fluid Dynamics (CFD) tool. Parametric studies are carried out to find out the thermochemical and hydrodynamic characteristics of the hot gas in the rocket motor nozzle. The performances of different supersonic and subsonic sections were studied in terms of the hydrodynamic aspects such as static pressure and Mach number distribution. It is observed that the tradeoff of implementing thrust vectoring mechanism amounts to an additional pressure loss of 10.06% in the rocket motor. Such analyses are specific to certain types of Short Range Ballistic Missiles (SRBM) having solid state propellant (primary stage) in radial boost, end burning pulsed configuration with exacting demands on maneuverability and control implied upon payload and mission criterion.Journal of Bangladesh Academy of Sciences, Vol. 41, No. 1, 69-84, 2017